Identification of knowledge management requirements in Bahraini schools - Rajab, Sharif Ali Hassan (Kulliyyah of Information & Communication Technology, International Islamic University Malaysia, 2017)
Knowledge is considered an essential resource contributing to the success of institutions today. Educational institutions can use knowledge management to improve efficiency of its processes and by understanding the potential of knowledge creation and sharing, the education of students and development of staff can be facilitated, and the school's management efficacy can be enhanced. Many schools have been facing problems caused by the rapid loss of knowledge and skills. This research has endeavored to set the foundation for a model of knowledge management to be followed in the schools of the Kingdom of Bahrain, according to the schools' needs; it also shows the need to recognize the reality of practicing knowledge management processes, review and follow-up processes and the availability of knowledge management requirements; the research then goes on to examine the effect of these variables on knowledge management processes. The research addresses the importance of knowledge management as a contemporary administrative concept that can help schools to raise their service level and finally be able to build a knowledgeable society. To achieve the objectives of the study, a questionnaire was designed and distributed to a sample of 550 (five hundred and fifty) teachers and administrators. Subsequently, the collected data was analyzed and the hypotheses were tested by using AMOS program backed by SPSS Ver.22. The validity and reliability of the instrument has checked by using Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). The research reached the following results:Thereis a statistical link betweenthe schools' needsand knowledge management requirements, which has a positive effect on knowledge management processes. In addition, there is also a connection between those requirements and the knowledge management processes. Furthermore, there is also a correlation between the review and follow-up processesand knowledge managementprocesses. Additionally, there is a bond between knowledge management requirements and review and follow-up processes that affect knowledge management processes. Finally, the statistical relation between the schools' needs and review and follow-upprocesses that influence knowledge management processes.Consequently, the research has come up with the following recommendations: Schools have to show interest in applying knowledge management processes and to provide the necessary requirements according to the schools' potential, focusing on the needs, and the necessity of review and follow-up so as to identify the shortcomings to deal with, and how to achieve success. As a rule, any project starts small and then grows, but the most important thing is to take responsibility and begin to solve the problems not leaving them to multiply.